Peran Public Speaking Reporter Dalam Pembuatan Konten Vidio Reportase English For Broadcasting - Sukma, Stevi Nanda; Eriend, Dion (CV. ITTC INDONESIA, 2024)
This final assignment aims to describe and understand the importance of the role of public speaking reporters in creating English reportage video content for broadcasting as well as their ability to speak English, especially in the field of broadcasting. Public speaking is related and closely related to a reporter. Public speaking is the art of speaking and processing words in front of a large audience. Public speaking comes from two words, namely